Measurement of the 230Th(n,f) cross-section at the CERN n_TOF facility - Michalopoulou, Veatriki; Diakaki, Maria; Eleme, Zinovia; Kokkoris, Michael; Patronis, Nikolaos; Stamatopoulos, Athanasios; Tsinganis, Andrea; Vlastou, Roza; collaboration, n_TOF (HNPS Advances in Nuclear Physics, 2022)
The study of neutron induced reactions on actinides is of great importance both for the design of advanced nuclear systems and for fundamental research. The design of Generation IV reactors, Accelerator Driven Systems (ADS), as well as the study of alternative fuel cycles, such as the thorium fuel cycle, highlight the need for accurate cross-section data. In addition, fission cross-section data can assist in the study of the fission process and the fission barrier. Specifically, 230Th is produced from the alpha decay of 234U in the thorium fuel cycle, thus its fission cross-section is required with high accuracy. In addition, in the fission cross-section of thorium isotopes narrow resonances and fine structures are present, which cannot be explained efficiently by the double-humped fission barrier. For 230Th, previous measurements have shown a resonance at 720 keV with additional fine structures. However, few discrepant experimental data exist in literature covering the energy region from the fission threshold up to 25 MeV. For these reasons, the fission cross-section of 230Th was measured at the CERN n_TOF facility, with the time-of-flight technique in order to cover the energy range of the previous measurements and extend the measurements to higher energies. The measurements were performed with Micromegas detectors, while the high purity 230Th were produced at JRC-Geel in Belgium. The analysis procedure for the cross-section results are on the final stages. In this work, a study on the angular distributions of 230Th, performed for the first time with this kind of Micromegas detectors is presented.